Circular business models: Current aspects that influence implementation and unaddressed subjects - Salvador, Rodrigo; Barros, Murillo Vetroni; Luz, Leila Mendes da; Piekarski, Cassiano Moro; de Francisco, Antonio Carlos (Journal of cleaner production, 2020)
Natural resources are limited and society has long been unwisely consuming them, while Earth has been longing for care. Most existing businesses are based on linear models and a transition to Circular Business Models is necessary. Circular Business Models are business models that enable systems that are regenerative by nature; they seek maintaining resource value at its maximum for as long as feasible, and eliminating or reducing resource leakage, by closing, slowing, or narrowing resource flows. For a transition to circular business models to happen, researchers and practitioners need to know how to implement and manage them. Therefore, this paper’s aim is threefold: (i) identify researchers, topics of highlight and journals housing research on Circular Business Models worldwide, (ii) identify the main aspects that influence Circular Business Model implementation, and (iii) point the unaddressed subjects in the existing literature on Circular Business Models. To that end, a systematic literature review was conducted. The EndNote, Microsoft Power BI, and the VOSviewer software tools were used to manage references and build visual maps, respectively. Resource flow management, considerations on surpluses, system orientation, challenges to circular business models, system design aspects, influence of company size, possible rebound effects, customer consideration, company’s culture and behavior, and capacity building for CE have been the main aspects of current concern on circular business model investigation. The importance of increasing circularity through circular business models is mainly addressed through the importance of top management support and its action from the company’s core to the outside. Further investigations and partnerships from theoreticians and practitioners are expected to assist the evolution of the theme. •CBM advance seems to have begun in 2014.•The main topics of current concern on CBM implementation are identified.•Subjects not addressed in the existing literature on CBM are pointed.